An Intersectional Feminist Study of the Selected Poems of Morgan Parker - Omar Esmaeel , Aram; Faiq Saeed, Zanyar (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
African-American women have experienced discrimination and subjugation throughout history. African-American authors have utilized their creative works to emphasize the mistreatment of African-American women. Morgan Parker is an author who endeavors to demonstrate the cultural subjugation inflicted upon African-American females in her literary works. Oppression in its many forms, such as gender, race, and class, can be seen in various cultural contexts. A feminist perspective with consideration for the intersections of race, gender, and other forms of social discrimination is used to comprehend the subject of cultural subjugation portrayed in the chosen poems. The importance of this paper lies in the fact that readers may become more conscious of and empathetic toward the mistreatment of African-American women throughout history when they are made aware of the multiple forms of oppression they have experienced. This may cause readers to consider taking action to ensure African-American women have a better quality of life.